AMIDO DE MANDIOCA OXIDADO POR PERÓXIDO DE HIDROGÊNIO COM PROPRIEDADE DE EXPANSÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
Native starches have characteristics that limit their application by industries. Among commercial starches, that extracted from cassava is considered abundant and economical and several studies considering its modification has been carried out with the aim of improving and enhancing industrial application.The oxidation is a form of modification that provides starches with low paste viscosity and increased expansion property. The use of metal ions has been reported by some authors to increase the efficiency of the oxidation process, but the incorporation of ions in starch granules also seems to occur. Another form of modification that is being studied is the acid-alcohol, due to the fact that alcoholic reaction medium allows the use of lower concentrations of acids. In order to improve and enhance the oxidation of starches, this study aimed to investigate the interference of pH, hydrogen peroxide concentration, reaction time and also the interaction of the starch granule with metal ions in the oxidation process. Preliminary tests were conducted for understanding the influence of Cu (II) and Fe (II) in starch oxidation, and their residues in the final product, through qualitative and quantitative instrumental analyses, besides being investigated contribution of pH and the concentration of hydrogen peroxide during the oxidation. From the preliminary tests a central composite rotatable design (CCRD) with 17 treatments and three central points was used to verify the influence of variables pH (2.30 to 5.70), H2O2 concentration (0.5 to 5.5 %, v/w, dry basis) and reaction time (28 to 62 min). Two methods were used for the oxidation, one using water and the other using anhydrous methanol as reaction medium in order to verify the behavior of the oxidation reaction. The effect of variables on the physicochemical properties was evaluated with use of Response Surface Method (RSM). The samples oxidized with the use of metal ions presented residues in the oxidized starch and the results with the use of Fe (II) showed a greater expansion and lower peak viscosity, being used for the entire planning. It was found by the RSM, that the pH, the concentration of hydrogen peroxide and the reaction time influenced the two methods of oxidation and the physicochemical properties of cassava starch. The cassava starch oxidized in aqueous media showed better results, regarding the physicochemical analyses, than those found in the oxidation in anhydrous medium. The best conditions found for oxidation in aqueous media were those of the central point (treatments 15,16 and 17) for the expansion property, carboxyl content and reducing power; for soluble solids at 50 and 80 ° C the best treatments were 4 and 13; for swelling power at 50 and 80 °C treatments 9 and 6, whereas for cycles of freezing and thawing, the treatment 5; in the case of paste property, the most pronounced change occurred in the treatment 7.For anhydrous methanol oxidation due to lack of fit of different models, it is difficult to establish which were the best conditions for the experiment and this methodology should be studied considering other variables in different alcohols 9 and starches, so it can be directly compared with the traditional oxidation is aqueous medium.
Keywords: oxidação; metanol anidro; planejamento experimental; DCCR; oxidation; anhydrous methanol; experimental planning; CCRD; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS